Das Totenschiff - Traven, B., 1882-1969 (Salt Lake City, UT : Project Gutenberg, 2025)
"Das Totenschiff: Die Geschichte eines amerikanischen Seemanns" by B. Traven is a novel written in the early 20th century. The book centers on the experiences of an American sailor who, after being left behind by his ship in Europe, struggles with statelessness and the bureaucratic nightmares faced by those without official papers. Through the eyes of its protagonist, the novel explores themes of alienation, identity, and the impersonal cruelty of modern institutions. The opening of the novel introduces the unnamed American sailor, recounting his recent voyage from New Orleans to Antwerp aboard the S.S. Tuscaloosa. After missing his ship's departure, he becomes trapped in a Kafkaesque maze of police interrogations, detention, and forced border crossings, all made worse by his lack of proper identification or seaman$1 (Bs papers. The narrative, laced with dry humor and irony, follows his attempts to find work or assistance, the indifference and coldness of officials, and the camaraderie (and occasional generosity) of ordinary people. From Antwerp to Rotterdam and across borders, the protagonist$1 (Bs predicament illustrates the vulnerability and invisibility of the working man in a world governed by paperwork and rigid national boundaries. (This is an automatically generated summary.)s
Wikipedia page about this book: https://de.wikipedia.org/wiki/Das_Totenschiff
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Death_Ship
Release date is 2025-04-19
Jens Sadowski and the Online Distributed Proofreading Team at https://www.pgdp.net. This book was produced from images made available by the HathiTrust Digital Library.
Keywords: Sea stories; Fantasy fiction